Gestão eclesiástica: os controles internos descentralizados para o centro de serviço compartilhado - Mendonça, Renato Camargo de (2012)
The Catholic Church is an ancient Institution which is present throughout the world. But times change and with this there must be an adaptation of his roles opposite the world that is in contrast change. Its management must have the inner vision of the institution and look for the external events that will give support to their pastoral work from happening. It is all over the world with the mission to evangelise and bring new conditions to each human being. It is necessary that have financial conditions and control over your expenses and costs for the continuation of the work that has been recognized worldwide in combating inequality and human promotion. There is a hierarchical structure of the Church that begins in Rome and spreads throughout the world. We enter this tiered context from the Holy See until we get the Particular Church, which in this case is the Diocese of São João da Boa Vista. To the pastoral, administrative controls within the decentralized system p To the pastoral, administrative controls within the decentralized system transitioning into a shared service Centre of the Diocese. Exploring your creation, deployment, and what the results achieved with the two system types. With the data raised, observed that there were no major economic progress, greater controls in processes and a beginning of change culture with regard to the set, i.e. decisions benefiting all business units. This cost savings should be applied in your activity so that it is evangelization